3D printing of a metal material on another dissimilar metal base - Tian, Jinmiao (Nanyang Technological University, 2023)
In the present day, 3D-printing, also known as additive manufacturing, has gradually become an upgrade and supplement for traditional manufacturing techniques. However, the thermal incompatibility during the material melting, cooling, and solidification stages gives rise to the formation of pores, cracks, brittle intermediate phases, and other defects in the fabricated components, leading to a degradation in bonding quality. So, in this context, how to successfully fabricate components using additive manufacturing techniques to melt and fuse a metal alloy onto a dissimilar metal alloy has become a key research aspect in this field. According to previous research, an interpenetrating interface morphology between the two dissimilar materials is a critical indicator for a good strength. In this project, the understanding of AM processing of bimetallic structures will be highlighted, and the experiment of selective laser melting technology would be employed to deposit the CoCrMo powders onto the base of the Inconel 625 (INC625). The tensile strength of INC625/CoCrMo components will be studied by making use of tensile testing. To evaluate the quality of the alloy-alloy interface in a quantitative manner, computational software ANSYS Workbench 2023R1 (LS-DYNA) would be used to simulate the tensile test process of additively manufactured metals. With the understanding of the relationship between additive manufacturing parameters and tensile strength of additively fabricated metals, it is able to customize the AM process to improve the material mechanical properties.